2020
DOI: 10.1108/caer-05-2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on China's agricultural trade

Abstract: PurposeThe outbreak of the novel COVID-19 virus has spread throughout the world, causing unprecedented disruption to not only China's agricultural trade but also the world's agricultural trade at large. This paper attempts to provide a preliminary analysis of the impact of the COVID-19 pandemic on China's agricultural importing and exporting from both short- and long-term perspectives.Design/methodology/approachThis study seeks to analyze how the outbreak of COVID-19 could potentially impact China's agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 11 publications
2
38
1
1
Order By: Relevance
“…A similar finding is obtained by Cao et al (2020), where the agricultural exports for China have been negatively impacted in the short-term due to the disruption of the supply chain. Furthermore, some studies expect that the high probability of the pandemic would lead to increasing non-tariff measures, posing limits to agricultural exports (Barichello, 2020;Cao et al 2020). Besides focusing on trade volume, Qin et al (2020) and Akter (2020) analyse the impact of Covid-19 on the volatility of commodity prices and food prices, respectively, and find that the current pandemic is expected to increase prices.…”
Section: Literature Reviewsupporting
confidence: 81%
See 3 more Smart Citations
“…A similar finding is obtained by Cao et al (2020), where the agricultural exports for China have been negatively impacted in the short-term due to the disruption of the supply chain. Furthermore, some studies expect that the high probability of the pandemic would lead to increasing non-tariff measures, posing limits to agricultural exports (Barichello, 2020;Cao et al 2020). Besides focusing on trade volume, Qin et al (2020) and Akter (2020) analyse the impact of Covid-19 on the volatility of commodity prices and food prices, respectively, and find that the current pandemic is expected to increase prices.…”
Section: Literature Reviewsupporting
confidence: 81%
“…The same is expected for the agricultural exports for China in the long-term due decline in demand for agricultural imports (Zhang et al, 2020;Barichello, 2020). A similar finding is obtained by Cao et al (2020), where the agricultural exports for China have been negatively impacted in the short-term due to the disruption of the supply chain. Furthermore, some studies expect that the high probability of the pandemic would lead to increasing non-tariff measures, posing limits to agricultural exports (Barichello, 2020;Cao et al 2020).…”
Section: Literature Reviewsupporting
confidence: 72%
See 2 more Smart Citations
“…Many studies have demonstrated emerging threats to global food security [62,143] and tremendous disruptions in agricultural supply chains [144,145] due to the pandemic. Notwithstanding that Wang et al [146] and Cao et al [147] expect that the impacts of supply disruption would be short-lived, development of warehousing and storage capacities at ports along the PSR should be considered a fundamental issue to ensure the sufficiency of safety stocks and inventories. The improvement of port infrastructure connectivity, logistics performance [68], and diversification in maritime routes [1] will allow China and its counterparts to avoid localized disruptions, establish a multiple-location trade network in the High North, and enhance the resilience of supply chains globally.…”
Section: Market Effectsmentioning
confidence: 99%